IMPLEMENTASI VISI MISI SMA NEGERI 2 REMBANG: MENJADI SEKOLAH ADIWIYATA NASIONAL SEBAGAI BENTUK EDUKASI UPAYA PENCEGAHAN DEFORESTASI - Zulfatun Nawfa (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Climate change is one of the triggers for disasters, if it continues, it is not impossible that in the next few years there will be many disasters in our country. One of the negative impacts of climate change is the occurrence of very extreme temperature changes, one of the causes is deforestation. For that, we need to make various efforts to prevent climate change, for example by processing waste, doing reforestation, and implementing electricity-saving behavior. All levels of society must of course participate in this activity, including institutions such as offices and schools. One of the efforts that schools can do is provide education to students about deforestation and how to prevent it. This study was written to determine the role of SMA N 2 Rembang in efforts to prevent deforestation carried out by the government, the research method used was through data collection from direct observation.